Molecular characterization, expression and antimicrobial activity of complement factor D in Megalobrama amblycephala. Issue 89 (June 2019) - Ding, Ming; Fan, Jun; Wang, Weimin; Wang, Huanling; Liu, Hong
Abstract: Complement factor D ( Df ) is a serine protease, which can activate the alternative pathway by cleaving complement factor B, and involves in the innate defense against pathogens infection in teleost. In this study, we cloned, characterized the Df gene from blunt snout bream ( Megalobrama amblycephala ) ( Mamdf ), and examined its expression pattern and antimicrobial activity. The open reading frame (ORF) of Mamdf was 753 bp, encoding 250 amino acids with a molecular mass of 27.2 kDa. Mamdf consisted of a single serine protease trypsin superfamily domain, 3 substrate binding sites and 3 active sites, but no potential N -glycosylation site. Pairwise alignment showed that Mamdf shared the highest identity (94%) with grass carp ( Ctenopharyngodon idellus ). Phylogenetic analysis indicated that Mamdf and other vertebrate Df had a common ancestral origin. Mamdf structured with 4 introns and 5 exons. The Mamdf mRNA expressed relatively high at the intestine appearance stage during early development and constitutively expressed in various tissues with the highest expression in the kidney in healthy adults. After challenged with Aeromonas hydrophila, significant changes of Mamdf at both mRNA and protein levels in the kidney, spleen, liver and head-kidney were observed. The recombinant Mamdf protein showed antimicrobial activity against both gram-positive bacteria and gram-negative bacteria. The above results suggested the immune function of Mamdf, and would benefit further detailed Df function research in the immune process in teleost. Highlights: Mamdf gene was identified and characterized in blunt snout bream. Mamdf expression was examined during early development and in adult tissues. Mamdf mRNA and protein levels were examined post A. hydrophila infection. Mamdf recombinant protein was obtained and its bacteriostatic activity was proved.